PENGARUH MANAJEMEN KONFLIK, PERUBAHAN ORGANISASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN - Jumawan Jumawan; Hadita, Berliana Febrianti, Diana Noviyanti, Damar Asmarani, Dyah Pratiwi, Evi Permatasari, Rahma Fi (Jurnal Ekonomi dan Bisnis, 2024)
Previous research or relevant research is very important in research or scientific articles. Previous research or relevant research functions to strengthen theories and phenomena of relationships or influences between variables. This article reviews the factors that influence employee performance, namely: Conflict Management, Organizational  Change  and  Organizational  Culture,  a  literature  study  on Organizational Change Management. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) Conflict Management influences employee performance; 2) Organizational changes affect employee performance; and 3) Organizational culture influences employee performance. Change is very important for organizations to experience (Gutama, 2010). This is because. The organization definitely also wants something new and definitely doesn't want it lagging behind other organizations. This is normal because of good organization is an organization that is able to follow the current developments of the times but does not leave behind the organization's distinctive image. As time goes by, changes and developments from time to time have progressed quite rapidly.